4D Seismic Bandwidth and Resolution Analysis for Reservoir Fluidflow Model Applications. Issue 1 (1st December 2019) - Souza, Rafael; Lumley, David; Shragge, Jeffrey; Davolio, Alessandra; Schiozer, Denis
Summary: Limitations on the vertical resolution in seismic data and fluid-flow models challenges the accurate interpretation of time-lapse (4D) seismic signals to identify fluid saturation changes within hydrocarbon reservoirs. Conventional streamer seismic data typically have a vertical resolution of 10-20 m at reservoir levels due to the lack of both lower and higher frequencies in the seismic spectrum, while fluid-flow simulations commonly run with significantly finer-scale vertical model grid spacings on the order of meters. Recently developed seismic acquisition methods (i.e., broadband seismic) have improved vertical seismic resolution relative to conventional acquisition by enhancing both the low- and high- frequency components. We investigate whether this improved seismic vertical resolution will result in potential benefits for fluid-flow and reservoir monitoring. We apply a synthetic 3D/4D seismic forward modelling procedure to the fine-scale fluid-flow model UNISIM-I-R, developed from observations of the Namorado field, Campos Basin, Brazil. Our procedure involves 4D seismic forward modelling, seismic amplitude map extraction, and quantitative 3D and 4D seismic amplitude analysis. Our results indicate that typical broadband seismic data can identify reservoir sands approximately 6 m thick in comparison to the 10-20 m commonly recovered in conventional seismic bandwidth. The improved seismic vertical resolution is closer to the fluid-flow model vertical grid spacing, which reduces seismic interpretation uncertainties associated with upscaling/downscaling procedures and ultimately improves the reliability of reservoir model predictions.